Evaluation of Office Administration Internship Program in Office Administration Education Study Program - Umam, Muhammad Choerul; Maureen, Irena Yolanita (Universitas Trunojoyo Madura, 2023)
The aim of this study is to provide an overview of the implementation of the Office Administration Internship Program in the PAP course. Additionally, this research aims to gather information about the obstacles and challenges faced when carrying out the internship, from planning to implementation. It is expected that comprehensive information will be gathered from various related parties, so that the results obtained can be used to design concurrent improvements and receive feedback to improve the quality of the placement organization in the future. The population of this study consists exclusively of sixth-semester students who have completed their internships, 35 partner agencies with staff related to the implementation of the internship, such as agency managers, internship supervisors, on-site lecturers as supervisors, and various policies related to the implementation of internships. Data collection was carried out using open and closed questionnaires, interviews, documentation, observation, and focus group discussions. The data analysis was carried out using qualitative descriptive analysis, comparative correlation analysis for bivariate analysis, and identification of inhibiting or supporting factors. Through this research, extensive feedback is expected to be gathered so that improvement efforts can be carried out simultaneously in accordance with each role and authority, while building higher quality synergistic collaborations.